Exploring the degree of influence of different advertisement role in enhancing brand image for higher learning institutions - Khan, Md. Ashraful Azam; Rahman, Muhammad Sabbir (The International Journal Research Publications, 2014)
This research inquiries about the effect of various forms of advertisement on enhancing brand image for higher learning institutions. The survey applied a questionnaire study of 250 respondents. Data were analysed thorough multiple regression analysis and other descriptive statistical techniques. The outcomes propose that online advertisement plays the most influential role in enhancing brand image for a higher learning institution followed by television advertisement and print advertisement. The research also notes that the management of higher learning institutions should consider online advertisement for their institutions to enhance the brand image. Yet, the researchers also agreed that the dominance of advertisement for higher learning institutions also requires television and print advertisement as well. The study contributes to the branding literature by relating with diverse manners of advertising under Malaysian higher learning institution’s students’ perspective.